Association between peripheral plasmablasts and postoperative exacerbation in patients with thymoma‐associated myasthenia gravis. Issue 2 (22nd January 2019) - Izaki, Shoko; Tanaka, Satoru; Oji, Satoru; Kubota, Akihiro; Fukaura, Hikoaki; Nakayama, Mitsuo; Nomura, Kyoichi
Abstract: Objective: Thymoma‐associated myasthenia gravis (TAMG) is a type of myasthenia gravis (MG) that has a higher likelihood of worsening in comparison with non‐TAMG, and MG symptoms often worsen after thymectomy. We measured peripheral T/B lymphocyte subsets before and after thymectomy in TAMG patients, and investigated the relationships with the occurrence of postoperative exacerbation of MG symptoms. Methods: Participants were 10 TAMG patients, 40 healthy controls and five other surgical control patients. Peripheral lymphocyte subsets were measured using FACS‐Canto flow cytometry before, and 1, 7, and 28 days after thymectomy in the TAMG, and before and 7 days after thymectomy in the other surgical control patients. Results: Natural killer cells modestly decreased, and plasmablasts increased significantly ( P  = 0.005) after 7 days postoperatively in comparison with preoperative values. Conversely, no obvious changes were observed in plasmablasts or natural killer cells in T/B lymphocyte subsets. From evaluation of postoperative clinical course and plasmablasts, exacerbation of MG symptoms was observed between 2 and 3 weeks after thymectomy in five of 10 patients (50%) of TAMG. In these five patients, plasmablasts markedly increased after thymectomy in three patients, among whom two patients had originally shown high plasmablast levels before thymectomy. There were also two patients who exacerbated without changes in plasmablast levels. Conclusions: In patients with exacerbation of neurological symptoms after thymectomy for TAMG, the plasmablast levels were originally high and/or became high postoperatively. Thus, elevated plasmablast levels could potentially be predictive of postoperative exacerbation of MG. Abstract : In thymoma‐associated myasthenia gravis patients, plasmablasts increased significantly at 7 days after thymectomy, compared with before thymectomy.